2008
DOI: 10.1088/0957-4484/19/24/245703
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of carbon nanotubes and reinforcing effects in nylon-6 polymer composite fibers

Abstract: Alignment of pristine carbon nanotubes (P-CNTs) and fluorinated carbon nanotubes (F-CNTs) in nylon-6 polymer composite fibers (PCFs) has been achieved using a single-screw extrusion method. CNTs have been used as filler reinforcements to enhance the mechanical and thermal properties of nylon-6 composite fibers. The composites were fabricated by dry mixing nylon-6 polymer powder with the CNTs as the first step, then followed by the melt extrusion process of fiber materials in a single-screw extruder. The extrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…Previous studies reported improved mechanical performance of conventional composites with the addition of nano fillers [119][120][121][122][123][124]. Researchers also verified that the toughness of the composite improves because of nano fillers [125,126].…”
Section: Multiscale Compositesmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies reported improved mechanical performance of conventional composites with the addition of nano fillers [119][120][121][122][123][124]. Researchers also verified that the toughness of the composite improves because of nano fillers [125,126].…”
Section: Multiscale Compositesmentioning
confidence: 84%
“…Moreover, the benefits of increasing delamination resistance in fiber reinforced composites have been proven using multiscale reinforcement, using fibers and CNTs together on the resin system or on the surface of the fibers [5,[119][120][121][122][123][124]. The ILFT of the multiscale composite is of further interest.…”
Section: Multiscale Compositesmentioning
confidence: 99%
“…Zhang et al found that after the CNT yarn was pulled through droplets of ethanol, the several centimeterwide yarn shrank into a tight fiber, typically 20-30 µm in diameter, and the strength of the CNT yarn dramatically improved. The CNT alignment was found to be crucial for fiber properties [93,94] and could be measured by Raman and X-ray diffraction (XRD) [95,96]. Zheng et al [97] observed a strong correlation between the array morphologies (the straightness of CNTs) and the fiber properties and well-aligned arrays yielded high performance, while wavy arrays led to poor performance.…”
Section: Carbon Nanofibers From Cnt Yarns By Dry Methodsmentioning
confidence: 99%
“…Several researches have also been reported considering different aspects of thermal, mechanical, electrical and rheological properties of nanocomposites which have used in situ polymerization, solution casting, melt spinning and melt compounding methods [3,4,[6][7][8][9]. Melt mixing of CNTs and thermoplastic matrices by single screw [10,11] or twin screw extruder [6,[12][13][14] is the most economical and desirable approach in comparison with other methods because, for fabricating these composites no additional equipment is needed. This process can be performed with conventional plastic machines, i.e.…”
mentioning
confidence: 99%
“…However, in some cases there would be no any other method to obtain a desired product. Rangari et al [10] reported that the tensile strength of PA6 fibre nanocomposites prepared by a single screw extruder, enhanced by 230% which contained only 1 wt% unmodified CNTs, while De Zhang et al [6] indicted that tensile strength improved by about 124% with the same CNTs loading using twin -screw mixer. Phang et al [14] have studied the effect of CNTs on crystallinity of the polymer matrix prepared via melt compounding.…”
mentioning
confidence: 99%